STATEMENT AND STUDY OF A BOUNDARY VALUE PROBLEM FOR A THIRD-ORDER EQUATION OF PARABOLIC-HYPERBOLIC TYPE IN A MIXED PENTAGONAL DOMAIN, WHEN THE SLOPE OF THE CHARACTERISTIC OF THE OPERATOR THE FIRST ORDER IS GREATER THAN ONE - MIRZA MAMAJONOV; XILOLA SHERMATOVA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this paper, we pose and study one boundary value problem for a third-order parabolic-hyperbolic equation of the form in the pentagonal region, when the characteristic of the operator more than one. The unique solvability of the problem posed is proved using the method of constructing a solution.